Azimuthal and vertical streaming instability at high dust-to-gas ratios and on the scales of planetesimal formation - Schreiber, Andreas; Klahr, Hubert (The astrophysical journal, 2018)
The collapse of dust particle clouds directly to kilometer-sized planetesimals is a promising way to explain the formation of planetesimals, asteroids, and comets. In the past, this collapse has been studied in stratified shearing box simulations with super-solar dust-to-gas ratio ϵ, allowing for streaming instability (SI) and gravitational collapse. This paper studies the non-stratified SI under dust-to-gas ratios from up to without self-gravity. The study covers domain sizes of , , and in terms of the gas-disk scale height using the PencilCode. They are performed in radial-azimuthal (2D) and radial-vertical (2.5D) extents. The used particles of and 0.1 mark the upper end of the expected dust growth. SI activity is found up to very high dust-to-gas ratios, providing fluctuations in the local dust-to-gas ratios and turbulent particle diffusion δ. We find an SI-like instability that operates in r-φ, even when vertical modes are suppressed. This new azimuthal streaming instability (aSI) shows similar properties and appearance as the SI. Both, SI and aSI show diffusivity at only to be two orders of magnitude lower than at , suggesting a relation that is shallow around . The (a)SI ability to concentrate particles is found to be uncorrelated with its strength in particle turbulence. Finally, we performed a resolution study to test our findings of the aSI. This paper stresses the importance of properly resolving the (a)SI at high dust-to-gas ratios and planetesimal collapse simulations, leading otherwise to potentially incomplete results.